Effect of sawdust powder - oil palm shell (ops) ash mixture on compressive strength of opc mortar - Tan, Mei Ling (2014)
There is an enormous amount of waste materials being disposed due to the growth of industrialization and urbanization nowadays. The high demand of cement in construction field has posed the researches to make use of these waste materials to serve as partial substitute material in cement. This study will be conducted- to evaluate the performance of sawdust and oil palm shell (OPS) on the mechanical properties of Ordinary Portland Cement (OPC) mortar. The aim of this research is to investigate the compressive strength, modulus of elasticity and workability of the cement mortar with various percentages of sawdust powder- OPS ash. Four types of mix design were prepared with the constant w/c of 0.40 and sawdust powder-OPS ash content of 1%, 2%, 3% and 4% are replaced the amount of cement respectively. 50% of fine sand is also required to be placed in the mixture so that the exact strength value can be. obtained during compressive testing. Curing 'was considered at the age of 7, 28, and 56 days. From the test, the slight increase of the strength of concrete with cement replacement showed when age increase. These results indicate that sawdust powder-OP ash can be applied to produce cement mortar with acceptable compressive modulus elasticity. This is a promising method with a friendly environment and economical effect.